Avulsion fracture of the posterosuperior tuberosity of the calcaneus managed with lag screw fixation. Issue 1 (February 2018) - Lui, T.H.
Highlights: It is an orthopaedic emergency as the fragment may impinge on the fragile skin of the posterior heel. The push of triceps surae will be significantly weakened. The fracture should be reduced promptly either by percutaneous or open method. Lag screw fixation should accompany an equinus short leg cast in order to hold the reduction. The surgeon should pay attention of the details of the operation and the rehabilitation program. Abstract: Background: To review the efficacy of lag screw fixation in management of avulsion fracture of the posterosuperior tuberosity of the calcaneus. Methods: Since 2002, thirteen patients with displaced fracture of the posterior tuberosity of the calcaneus were treated with emergency reduction of the fracture and lag screw fixation. The medical records and radiographs of the patients were reviewed and the patients were assessed according to the Kerr calcaneal fracture scoring system during the latest follow up. Results: There was no skin necrosis, but one wound dehisced in a patient with unstable diabetes and hypothyroidism. All fractures healed, but two had separation of the fracture fragments after the plaster was removed, both of them were elderly osteoporotic patients. The overall average calcaneal score was 93 (range, 77–100). The average calcaneal score of the patients with closed reduction was 91 (range, 77–100). The average calcaneal score of the patients with open reduction was 94 (range, 79–100). Complications occurred in seven patients (54%). Conclusions: Percutaneous or open reduction of the avulsion fracture of the posterosuperior tuberosity of the calcaneus together with lag screw fixation and equinus short leg cast immobilization can provide good results without skin necrosis. The surgeon should pay attention of the details of the operation and the rehabilitation program in order to minimize the complications.